Pesticide Exposure, Neurobehavioral Symptoms, and Neurobehavioral Performance in Pesticide Applicator in West Java, Indonesia - Liem, Jen Fuk; Frendy, Holie; Handoko, Yusuf; Hudyono, Johannes; Sutanti, Yosephin Sri (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
It was known that pesticide applicators are at risk of experiencing neurotoxicity and neurobehavioral alterations related to occupational pesticide exposure. This study aims to evaluate the association between pesticide exposure and the neurobehavioral performance of pesticide applicators in West Java, Indonesia where chemical pesticides were heavily used. We conducted a cross-sectional study in a vegetable farming center in West Java Province, Indonesia. A total of 88 pesticide applicators were included in the study on November 2022. A structured interviewer-administered questionnaire was used to obtain the participants’ characteristics. We performed the German Q18 questionnaire to screen the neurobehavioral symptoms and the WHO Neurobehavioral Core Test Battery (NCTB) for each participant to identify the neurobehavioral performance among pesticide applicators. Data were summarized descriptively and statistical analysis using chi-square and independent sample t-test was performed. We found that the most common neurobehavioral symptoms were symptoms related to memory, concentration, and fatigue. Poor neurobehavioral performance was found in 29.5% of participants and it was found to be associated with those grouped at age ≥ 44 years and categorized as having a high CEL. The pieces of evidence presented here suggest that neurobehavioral performance was associated with pesticide exposure.